La apropiación de los valores solidaridad y respeto y su influencia en el comportamiento social de los estudiantes de tercero de bachillerato general unificado - Prado García, Angélica Mariel (2018)
The purpose of the research project is to strengthen the values of solidarity and respect and its influence on the social behavior of the students of third of BGU of the educational unit Republic of France. Having as a central problem the deficient practice of values such as solidarity and respect and its influence on social behavior? The research starts from a current problem in contemporary society: the importance of the appropriation of values in the new generations for the formation of a social behavior.